2021
DOI: 10.1093/irap/lcab003
|View full text |Cite
|
Sign up to set email alerts
|

Hedging and grand strategy in Southeast Asian foreign policy

Abstract: This article examines recent interest in hedging as a feature of international politics in the Asia Pacific. Focusing on the small states of Southeast Asia, we argue that dominant understandings of hedging are misguided for two reasons. Despite significant advances in the literature, hedging has remained a vague concept rendering it a residual category of foreign policy behavior. Moreover, current accounts of hedging tend to overstate the strategic intentions of ostensible hedgers. This article proposes that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Third, these elements are clearly reflected in hybrid behaviour over issues like trade and security, especially in regional contexts such as East and Southeast Asia (see Hwang & Ryou‐Ellison, 2021; Jones & Jenne, 2021). The same is true of global issues, as with climate change, where the EU sided with the US normative agenda at COP 21 in Paris, only to cleave towards China's agenda at COP 26 in Glasgow.…”
Section: Fuzzy Bifurcation and The Distinguishing Features Of Hybriditymentioning
confidence: 99%
“…Third, these elements are clearly reflected in hybrid behaviour over issues like trade and security, especially in regional contexts such as East and Southeast Asia (see Hwang & Ryou‐Ellison, 2021; Jones & Jenne, 2021). The same is true of global issues, as with climate change, where the EU sided with the US normative agenda at COP 21 in Paris, only to cleave towards China's agenda at COP 26 in Glasgow.…”
Section: Fuzzy Bifurcation and The Distinguishing Features Of Hybriditymentioning
confidence: 99%
“…Managers fail to think strategically and employ new superior strategies in the face of increased competition and environmental turbulence (Rowe, 2014). Consequently, managers' greatest challenge is planning strategically that will ensure continued success in the future and which gives the firm a sustainable competitive edge over its competitors (Jones & Jenne, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The term “hedging” was introduced into the international relations (IR) lexicon in the 1990s, when scholars and commentators began using the term to describe state behavior in which a country takes a middle position between the two straightforward strategies of balancing and “bandwagoning,” displaying mixed elements of selective engagement, limited resistance, and partial deference (Lake 1996 ; Green 1999 ; Johnston and Ross 1999 ; Medeiros 2005 ; Goh 2005 ; Kuik 2008 , 2020 ). Although hedging has been in use for decades, it remains a highly contentious and widely misunderstood concept in both policy and academic circles (Lim and Cooper 2015 ; Wang 2018 ; Ciorciari and Haacke 2019 ; Shambaugh 2020 ; Tan 2020 ; Jones and Jenne 2021 ).…”
Section: Introduction: (Mis)understanding Hedgingmentioning
confidence: 99%
“…While a growing number of studies offer different conceptualizations and cover a range of diverse hedging cases (Tessman 2012 ; Tunsjo 2013 ; Jackson 2014 ; Fiori and Passeri 2015 ; Kuik 2016a , b ; Hoo 2016 ; Murphy 2017 ; Koga 2018 ; Ciorciari 2019 ; Korolev 2019 ; Lim and Mukherjee 2019 ; Liao and Dang 2019 ; Pitakdumrongkit 2020 ; Chan 2020 ; Teo and Koga 2021 ; Cao 2021 ), there is still no consensus as to how hedging should be defined and applied. Jurgen Haacke ( 2019 ) observed that “as the literature on hedging has expanded, the concept’s analytical value is no longer obvious.” David Martin Jones and Nicole Jenne ( 2021 ) have criticized the dominant understandings of hedging, arguing that the term remains “a vague concept rendering it a residual category of foreign policy behavior.”…”
Section: Introduction: (Mis)understanding Hedgingmentioning
confidence: 99%